Relationship between Agriculture Subsidy and Agricultural Production in Nepal - Paudel, Udgar Kumar (Curriculum Development Journal, 2024)
This article aims to analyze the relationship between agriculture subsidy and agricultural production in Nepal using annual time series data from 2013/14 to 2022/2023 A.D. Agricultural production is taken as the dependent variable and agricultural subsidy as the independent variable and it is analyzed using Karl Pearson Correlation and Ordinary Least Square (OLS) regression. The article found a high positive correlation (r= 0.72) among variables. Also, there exists a significant and positive relationship between agricultural production and agricultural subsidy (p-value =0.01) (Coefficient= 0.15) at a 5% level of confidence interval. Likewise, the residuals are free from heteroskedasticity and serial correlation. The article concludes that while the government should maintain its subsidy program, efforts must be made to address and control the irregularities in its distribution.